Portrait of Contemporary á¸¤adith Commentary Book: A Study of The Book Faá¹á¸¥ al-Munâ€˜Ä«m Syará¸¥ á¹¢aá¸¥Ä«á¸¥ Muslim By MÅ«sÄ SyÄhÄ«n LÄsyÄ«n - Bin Ja'Far, Hasbullah; Suparmin, Sudirman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The book â€œFatá¸¥ al-Munâ€™im Syará¸¥ á¹¢aá¸¥Ä«á¸¥ Muslimâ€ by MÅ«sÄ SyÄhÄ«n LÄsyÄ«n is one of the contemporary hadith commentary books. This research aims to discuss the commentary book, starting from the question: what is the portrait of the book Fath al-Munâ€™im as a contemporary hadith commentary book. This research is qualitative in nature. It is categorized as library research or literature study, with the primary source being the book Fatá¸¥ al-Munâ€™im. The research was conducted using a content analysis approach, which involves an in-depth discussion of the content of the book Faá¹á¸¥ al-Munâ€™Ä«m; a quick overview of the entire book and a careful reading of selected random chapters. The results of this research indicate that the portrait of the book Fatá¸¥ al-Munâ€™im as a contemporary hadith commentary book is reflected in its commentary subject matter that follows current trends, its well-organized and systematic structure, and its diverse methods and approaches